The Advancement of Digital Tools in Heritage Education - Venturo Huares, Rocío Verna (2025)
This article aimed to conduct a bibliographic review of the progress of new technologies related to heritage education, showing some examples of the experiences around it, reviewing its development and considering the advantages and limitations of its application; likewise, the digital gaps that hinder its expansion were considered. In this study, the descriptive documentary research method was used, making use of a narrative review, which includes documents that show the concepts of heritage and heritage education, pointing out their advances and new trends, also describing the characteristics of the new technologies used in the field of heritage education. The study concluded that the use of new technologies facilitates the dissemination of cultural and natural heritage, in addition to enabling a better development of meaningful learning, achieving reflective and critical skills in students, thus fostering creativity and interest in their past.